KEPUASAN KELUARGA PASIEN TERHADAP WAKTU TUNGGU PELAYANAN DI INSTALASI RAWAT JALAN RUMAH SAKIT JIWA PROVINSI KALIMANTAN BARAT - , Bambang Tri Wahono, dr. Tjahjono Kuntjoro, MPH, DrPH. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Waiting time for service is a problem frequently encountered in the practices of health service. The waiting time is one of the service quality aspects. If it can be managed well, the outcome will be patient satisfaction. However, the number of outpatient visits in the Mental Hospital of West Kalimantan Province continuously decreases, particulary in the last three years. Objective: This study is to find out the everage waiting time for service and the correlation between patient family satisfaction and the waiting time for service at the Outpatient Installation in the Mental Hospital of West Kalimantan Province. Method: It was an analytical survey with a cross-sectional design. Sample of the study was patient family consisting of 70 respondents selected using a purposive sampling method. The data were collected using two research instrument, i.e. questionnaires on patient family, waiting time for service, and patient satisfaction, and an interview guide for respondents. The data collected were analyzed by using a univariate analysis technique to find out the characteristics of respondent, and the average scores of waiting time for service and patient satisfaction, while a bivariate analysis was done using a chi square test and logistic regression test for multivariate analysis. Result: The average waiting time for service at Outpatient Installation in the Mental Hospital of West Kalimantan Province was in a âlongâ category. There was a correlation between waiting time for service and patient family satisfaction (p<0.05). The patient family with a quicker waiting time for service had a higher satisfaction. Conclusion: Waiting time for service is one of aspect of quality service. Most patient family at the Outpatient Installation in the Mental Hospital of West Kalimantan Province were satisfied with waiting time for service. Long waiting time for service, which can cause decrease in patient family satisfaction.